The Curious Case of Juhan Paju and a Fortunate Choice of Pop Lit over Poetry - Katre Talviste (Caietele Echinox, 2022)
This essay proposes a study of the poetics and local generic context of the work of Juhan Paju (1939–2003), arguably one of the very few original Estonian crime writers emerged from the twentieth century. The focus is on five of his novels centred on investigations led by Toivo Kivistik, a small-town police detective. The series is set in the last decades of the twentieth and the early years of the twenty-first century. This tumultuous period in local history has provided rich material for socially relevant themes. Paju’s work is original in treating this material, but also in his experiments with generic conventions, which he progressively adapts to his own talent and to the local context.